1998
DOI: 10.1097/00002820-199812000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring empathy as a variable in the evaluation of professional development programs for palliative care nurses

Abstract: Research indicates that empathy, a quality regarded as fundamentally important to nursing practice, is a teachable skill. Because empathic nurse-patient relationships are particularly important in the care of the terminally ill, this has direct relevance to the professional development of palliative care nurses. This article discusses the place of empathy as a criterion variable in the evaluation of a professional development program for palliative care nurses introduced at the Centre for Mental Health Nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 27 publications
1
30
1
Order By: Relevance
“…Inservice training was influential in this study in increasing the nurses' empathy levels, in agreement with the literature (Chant et al, 2002;Gysels et al, 2005;Yates, Hart, Clinton, McGrath, & Garthy, 1998). However, some studies found limited or no change (as cited in Kruijver et al, 2000;Razavi & Delvaux, 1997;Watson et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…Inservice training was influential in this study in increasing the nurses' empathy levels, in agreement with the literature (Chant et al, 2002;Gysels et al, 2005;Yates, Hart, Clinton, McGrath, & Garthy, 1998). However, some studies found limited or no change (as cited in Kruijver et al, 2000;Razavi & Delvaux, 1997;Watson et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…1988, Nardi 1990, Wilt et al. 1995, Yates et al. 1998, Cutcliffe & Cassedy 1999, Oz 2001, Beddoe & Murphy 2004, Ancel 2006).…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear whether this improvement was sustained. In an Australian study of palliative care nurses ( n = 181), it was reported that increased empathy was sustained three months after the completion of the programme (Yates et al. 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26] The concept of empathy was originally considered in the work of Carl Rogers. It is generally accepted that the quality of empathy is central to caring competence, because it fulfils important nursing goals, such as effective patient-nurse relationships.…”
Section: Empathy Skills In Nursing Educationmentioning
confidence: 99%